The Influence of Brand Image, Lifestyle and Word of Mouth (WOM) on Purchasing Decisions for N-Max Motorbikes - Putra, Reza Eka; Yanti, Sri (Zona Manajerial: Program Studi Manajemen (S1), 2022)
The purpose of this study is to find out and analyze the influence of brand image, life style and word of mouth on the purchase decision of N-Max motorcycles at yamaha PT dealers. Graha Auto Perkasa. The method used in this study is to use quantitative methods in associative approaches or studies. The population in this study was N-Max motorcycle users from 2019-2021 with a total of 5274 people, the sample of this study was 100 respondents. The collection technique used in this study used a questionnaire / questionnaire that was tested for validity and reliability, the data analysis technique of this study used Multiple Linear Regression, Classical Assumption Test, Hypothesis Test (t Test and F Test) and Coefficient of Determination. Data processing in this study used the SPSS Software version 25 program. The results of this research show that the brand image has a positive and significant effect on the decision to buy N-Max motorcycles at yamaha PT dealers. Graha Auto Perkasa Batam with a probability value of 0.038 < 0.05. Life style has a positive and significant effect on the purchase decision of the N-Max motorcycle at yamaha dealer PT. Graha Auto Perkasa Batam with a probability value of 0.000 < 0.05. Word of mouth negatively and significantly affects the purchase decision of N-Max motorcycles at yamaha dealer PT. Graha Auto Perkasa Batam with a probability value of 0.000 < 0.05. The coefficient of determination value of 81.1% shows the contribution of brand image, life style, and word of mouth (WOM) to purchasing decisions and the remaining 18.9% is influenced by various other variables.